The effects of berberine supplementation on cardiovascular risk factors in adults: A systematic review and dose-response meta-analysis - Zamani, Mohammad; Zarei, Mahtab; Nikbaf-Shandiz, Mahlagha; Hosseini, Shabnam; Shiraseb, Farideh; Asbaghi, Omid (Frontiers in Nutrition, 2022)
Cardiovascular disease (CVD) is a major concern today. Herbal medicine is one helping way to control CVD risks. One conclusive of herbal medicine is Berberine (BBR) and converse about it still exists, to clarify this issue, this meta-analysis was performed. PubMed/Medline, Scopus, and Web of Science were searched for RCTs in adults on the effect of BBR supplementation on CVD risk factors up to July 2022. The pooled results showed BBR significantly reduced triglyceride (WMD=-23.70 mg/dl; 95%CI -30.16,-17.25;P<0.001), total cholesterol (WMD=-20.64 mg/dl; 95%CI -23.65,-17.63;P<0.001), low-density lipoprotein WMD=-9.63 mg/dl; 95%CI, -13.87,-5.39;P<0.001), fasting blood glucose (FBG) (WMD=-7.74 mg/dl; 95%CI -10.79,-4.70; P<0.001), insulin (WMD=-3.27 mg/dl; 95%CI -4.46,-2.07;P<0.001), HbA1c (WMD= -0.45%; 95%CI -0.68,-0.23;P<0.001), HOMA-IR (WMD=-1.04; 95%CI -1.55,-0.52; p<0.001), systolic blood pressure (WMD=-5.46mmHg; 95%CI -8.17,-2.76;P<0.001), weight (WMD=-0.84;95%CI -1.34,-0.34;P<0.001), body mass index (WMD=-0.25 kg/m2; 95%CI -0.46, -0.04;P=0.020), while increased high-density lipoprotein (HDL) (WMD=1.37 mg/dl; 95%CI 0.41,2.23;P=0.005). The optimal dose of BBR was 1 g/day for TG, TC, and weight, 1.8 g/day for insulin and HOMA-IR, and 5 g/day for HDL. FBG's most efficient time frame was 40 weeks from the beginning of supplementation, whereas DBP and waist circumference was 50 weeks. In conclusion, the lipid profile, FBG balance, obesity parameters, and SBP were improved with BBR supplementation.